1975
DOI: 10.3109/07435807509053836
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Pre-Ovulatory Proestrous Gonadotropin Surge, Ovulation and Pregnancy with a Peptide Analogue of Luteinizing Hormone Releasing Hormone

Abstract: D-[PHE]-2-D[ALA]-6-LRH (Wy-18,185), an analogue of synthetic hypothalamic LRH, was evaluated for its anti-fertility properties. The compound dampens the preovulatory proestrous surge of serum LH and FSH in rats, is an active anti-ovulatory agent in both rats and rabbits and prevents pregnancy when administered pre-coitally to rats. Additionally, the compound suppresses the ovulatory event in rats only during the cycle in which it is acutely administered, does not interfere with the rat vaginal cycle and is dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 15 publications
(4 reference statements)
2
37
0
Order By: Relevance
“…In addition, leiomyomas in women of reproductive age are commonly treated with hormone ablative therapies such as GnRH agonists [11]. Treatment with these agents results in the shutdown of ovarian hormone production by inhibiting the release of gonadotropins by the pituitary and the halting of follicular development in ovaries [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, leiomyomas in women of reproductive age are commonly treated with hormone ablative therapies such as GnRH agonists [11]. Treatment with these agents results in the shutdown of ovarian hormone production by inhibiting the release of gonadotropins by the pituitary and the halting of follicular development in ovaries [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the ability of such analogs to stimulate or inhibit LH and FSH release, both antagonist and superagonist analogs have potent antigonadal and antifertility actions, suggesting that these compounds may be useful as reversible contraceptive agents (11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…At a single dose of 400 µg, Peptides 1, 2 and 5 exhibited considerable intrinsic activity (Table 2). Corbin & Beattie (1975) also reported that Peptide 3 possessed agonistic as well as antagonistic activity, but the agonistic activity was not strong enough to induce ovulation in Nembutal-blocked pro-oestrous rats, even when the i.v. dose was as high as 100 µg.…”
Section: Rat Experimentsmentioning
confidence: 99%
“…Several analogues based on the original decapeptide sequence have been synthesized and found to have weak but significant inhibitory properties (Vilchez-Martinez et ai, 1974a). However, it was the discovery of several agonistic analogues of LH-RH that were far more potent than the natural hormone that enabled a variety of relatively strongly active antagonistic peptides to be developed with structures based on the super-active analogues (Coy et ai, 1973(Coy et ai, , 1974VilchezMartinez et ai, 1974b;de la Cruz et ai, 1975de la Cruz et ai, , 1976aCorbin & Beattie, 1975). Most of these ana¬ logues, however, possess residual inherent LH-RH activities, which may overcome their LH releaseinhibiting activities, resulting only in partial blockade or no blockade of ovulation in animals.…”
Section: Introductionmentioning
confidence: 99%